Photoprotective Activities of Standardized Anredera scandens (L.) Moq. Leave Extract: an In-Vitro Study on UVB Absorption and UVA Protection - Samirana, Putu Oka; Nugraha, I Gusti Agung Anom Krisna; Putra, Anak Agung Gede Rai Yadnya (Jurnal Ilmiah Medicamento, 2026)
Background: Skin cancer is a worldwide disease caused by exposure to ultraviolet radiation, both UVA and UVB rays. Interest in discovering new natural ingredients with photoprotective activity has increased research to find plants containing high amounts of phenolic and flavonoid compounds. Objective: This research aimed to assess the in vitro photoprotective activity of ASL (ethanol extract of Anredera scandens (L.) Moq. leaves) standardized based on the Indonesian Herbal Pharmacopoeia. Methods: Extraction was performed using the maceration method with 70% ethanol as the solvent. Parameters used to determine quality are drying loss, water content, total ash content, acid insoluble ash content, total flavonoid content, and total phenolic content. Photoprotective activity against UVB rays was determined by measuring SPF value using the Mansur spectrophotometric method, while activity against UVA rays was tested using the trans-resveratrol degradation model. Results: Results indicate that ASL extract fulfilled quality requirements based on total flavonoid content (9.983 ± 0.090%) and total phenolic content (13.098 ± 0.611%). The SPF value was increased proportional to the increase in concentration. The sample showed an SPF value of 5.96 when tested at a concentration of 200 µg/mL. SPF value reached 27.9 at 1,000 µg/mL. The UVA photoprotection assay indicated that the ASL extract provided limited protection against trans-resveratrol degradation, with a reduction of 18.90%, which was lower than the positive control but still significantly better than the negative control. Conclusion: ASL extract can be developed as a candidate for a natural-based photoprotective active ingredient, used as a single agent or supportive component for sunscreen products.